Effectiveness of realistic mathematics worksheets with balinese cultural content on fourth-grade students' learning outcomes - Witraguna, Kadek Yudista; Ni Nyoman Tri Wahyuni; Putu Ayu Septiari Dewi (Universitas Kanjuruhan Malang, 2025)
This study examines the effect of Balinese culture-based Student Worksheets (LKPD) on fourth-grade students’ mathematics learning outcomes. Using a one-group pretest-posttest design, 30 students from SD Negeri 1 Kemenuh participated in the study. The LKPD was designed by integrating mathematical concepts with Balinese cultural contexts, such as traditional dances and architecture, to make learning more engaging and relevant. Data were collected through pretests and posttests. The results showed a significant improvement in posttest scores (t = 18.49, p < 0.05), indicating that cultural integration helps students understand mathematical concepts more concretely and boosts learning motivation. The findings suggest that culture-based LKPD can be an effective tool in elementary mathematics instruction. However, effective implementation requires the active role of teachers in connecting mathematical concepts with the local cultural environment of the students